Management of Muhammadiyah Student’s Character Education - Rahayuningsih, Puji; Sugianik, Dwi; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The cadre system used at Aisyiah Bukit Kemuning Elementary School is described in this study, as is the implementation of Muhammadiyah cadre education at Aisyiah Bukit Kemuning Elementary School in building student’s morale. Researchers prioritized appreciation in this study, taking a qualitative approach based on phenomenological philosophy. From the researcher's perspective, qualitative methods seek to understand and interpret the meaning of human behavior interaction events in specific situations. This study, which employs a phenomenological approach, focuses on the phenomena of Muhammadiyah educational institutions that carry out Muhammadiyah cadre activities. The implementation program in this case is carried out at Aisyiah Bukit Kemuning Elementary School. According to the study's findings, the implementation of Muhammadiyah cadre education management at Aisyiah Bukit Kemuning Elementary School contributed to students' moral formation. The development of Muhammadiyah cadres in schools based on management principles is more efficient and effective in character formation, resulting in changes in the personalities of students who have participated in cadre training.